2013
DOI: 10.1002/pssa.201300093
|View full text |Cite
|
Sign up to set email alerts
|

Transport behaviour of boron delta‐doped diamond

Abstract: The electrical transport properties of two-dimensional (2D) borondoped delta layers were investigated by a comprehensive analysis of physical, electrochemical and microscopic methods. The boron concentration profile was determined physically by elastic recoil detection (ERD) and compared to the doping (acceptor) profile extracted from capacitance-voltage (CV) measurements, giving a boron concentration of 2-4 Â 10 13 cm À2 . Corresponding field effect transistor (FET) characteristics, based on the boron-doped d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
3
15
0
2
Order By: Relevance
“…At 200 K, l $ 0.3 cm 2 /V.s. Recently, such low mobility values (0.01 cm 2 /V.s to 0.1 cm 2 / V.s) with comparable sheet carrier densities (2 to 4 Â 10 13 cm À2 ) were reported 13 for delta layers, where the conduction was demonstrated to occur by a variable range hopping mechanism (with a hopping exponent of 1/4). In our case, a conventional hopping exponent such as x ¼ 1, x ¼ 1/4, or x ¼ 1/2 was not found, so that a clear determination of the hopping type (respectively, nearest-neighbour, Mott or Efros-Shklovskii variable range hopping) was not possible.…”
Section: Hall Effect and Sheet Resistance Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…At 200 K, l $ 0.3 cm 2 /V.s. Recently, such low mobility values (0.01 cm 2 /V.s to 0.1 cm 2 / V.s) with comparable sheet carrier densities (2 to 4 Â 10 13 cm À2 ) were reported 13 for delta layers, where the conduction was demonstrated to occur by a variable range hopping mechanism (with a hopping exponent of 1/4). In our case, a conventional hopping exponent such as x ¼ 1, x ¼ 1/4, or x ¼ 1/2 was not found, so that a clear determination of the hopping type (respectively, nearest-neighbour, Mott or Efros-Shklovskii variable range hopping) was not possible.…”
Section: Hall Effect and Sheet Resistance Resultsmentioning
confidence: 91%
“…This was explained by a two carrier-type model, 17 but the corresponding devices did not yield any improved performance. Scharpf et al 13 reported delta-layers with very low sheet carrier densities (2 to 4 Â 10 13 cm À2 ) also showing very low mobility ranging between 10 À2 cm 2 /V.s and 10 À1 cm 2 /V.s. A model based on hopping and tunneling processes was proposed to explain these mobility values.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Measurement methods of the δ‐doping density are described in refs. . Metal contacts – The contact and wiring pattern was then transferred onto the wafer, by means of standard optical lithography and lift‐off deposition by e‐beam evaporation of titanium and gold, with a thickness of 100 nm each. Passivation – The wafer was spin‐coated with a 5 μm thick SU‐8 photoresist (MicroChem Corp. Westborough, MA, USA). Opening – The pattern transfer for opening the active area of the electrodes and the contact pads, was performed by optical lithography followed by ashing in O 2 /CF 4 plasma to remove thin insulating residues. A hard bake step was run at 190 °C for 20 min for curing the SU‐8 resist, thus providing superior chemical inertness and long life.…”
Section: Methodsmentioning
confidence: 99%
“…Only recently has a diamond growth system been specifically designed for delta doping using very smooth starting diamond substrates. It has shown promising initial results, detailed in works by Butler and Lobaev et al For the first time to these authors’ knowledge resistances <10 kΩ sq −1 (1.1 to 7 kΩ sq −1 ) with mobilities from 16 to 120 cm 2 V −1 s −1 (approaching the predicted mobilities of 150 to 200 cm 2 V −1 s −1 ) have been consistently obtained. Their experimental setup is similar to others.…”
Section: Conductive Diamond For Fetsmentioning
confidence: 99%